Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

Better stories for a gender equal and fairer social recovery from outbreaks: learnings from the RESISTIRÉ project - Strid, Sofia; Schrodi, Colette; Cibin, Roberto (Gender & Development, 2022)
La pandémie a radicalement modifié l’organisation de la société, avec une augmentation du travail à domicile, de l’enseignement à domicile et de la présence en ligne, le tout avec des implications spécifiques (non)intentionnelles sur le travail de soins rémunéré et non rémunéré. Ces implications, comme celles d’autres crises, sont sexistes et se manifestent selon le sexe, l’âge, le handicap, l’origine ethnique/la race, le statut migratoire, la religion, la classe sociale et les intersections entre ces inégalités. Si de nombreuses études ont identifié ces impacts inégaux et négatifs et soulignent d’importantes inégalités liées aux soins, la contribution spécifique de cet article est différente, à savoir celle de mettre en évidence des pratiques inspirantes comme de meilleures histoires de et dans le domaine des soins pendant la pandémie. L’objectif est de rendre ces meilleures histoires visibles et de les considérer comme des moyens d’atténuer les impacts inégaux de la COVID-19 et de ses réponses politiques. Théoriquement, l’approche est basée sur les « meilleures histoires », telles que développées par Dina Georgis (2013, Better Story. Queer Affects from the Middle East , New York : State University). L'article utilise des données quantitatives et qualitatives, recueillies auprès des 27 États membres de l'UE, de l'Islande, de la Serbie, de la Turquie et du Royaume-Uni, dans le cadre du projet européen H2020 RESISTIRÉ.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; covid-19; europe; intersectionnalité; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail du care

Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

Gender differences in emotional response to the COVID‐19 outbreak in Spain - García‐Fernández, Lorena; Romero‐Ferreiro, Verónica; Padilla, Sergio; David López‐Roldán, Pedro; Monzó‐García, María; Rodriguez‐Jimenez, Roberto (Brain and Behavior, 2021)
We aim to explore the differential presence of symptoms of anxiety, depression, and acute stress between men and women during the COVID-19 outbreak, and to study the relationship between these symptoms and two environmental variables, coexistence, and violence.We conducted a cross-sectional study starting on March 29 to April 5, 2020, based on a national online survey using snowball sampling techniques. Symptoms of anxiety (Hamilton Anxiety Scale), depression (Beck Depression Inventory), and acute stress (Acute Stress Disorder Inventory) were assessed. Differences in the presence of symptoms and the relationship of coexistence and domestic violence were evaluated from a gender perspective.Men showed significant lower mean (SD) in anxiety, depression, and acute stress levels than women [HARS, 14.1 (9.8) versus. 18.4 (10.2), F = 56.2, p < .001; BDI 3.4 (3.9) versus 4.5 (4.3), F = 16.6, p < .001, and ASDI 3.6 (2.9) versus 4.7 (3.1), F = 39.0, p < .001, respectively), as well as a weaker depressive syndrome (28.1% males versus 39.9% females, χ2 = 25.5, p < .001). In addition, an interaction Gender × Coexistence was found in anxiety (F = 56.2, p < .001) and acute stress (F = 3.52, p = .06) and, according to depressive symptoms, an interaction Gender × Violence was found marginally significant (F = 3.3, p = .07).Findings indicate that women present greater severity in symptoms of anxiety, depression, and acute stress. Moreover, loneliness and violence specifically worsen the emotional state in women. These results can undoubtedly guide better healthcare planning adopting a gender perspective.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; covid-19; espagne; europe; genre; périodes historiques; ressource en ligne; régions géographiques; santé; thématiques; violences; violences conjugales; étude quantitative

Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques

Bousso : maternité et bipolarité - Tant que je serai Noire
Tant que je serai Noire c'est le podcast qui répond à la question Tant que je serai Noire, serai-je mère ? Tant que je serai Noire ce sont des récits de femmes qui nous parlent de leur désir ou non désir d'enfant. Un Podcast qui nous montrent à quel point les récits des femmes interrogées st aussi intéressants que les 1000 vies de Maya Angelou. Je suis Tsippora la créatrice et productrice de Tant que je serai Noire. Retrouvez un lundi sur 2 un épisode. *** 📣 Pour cet épisode, je reçois Bousso, professeur d'anglais, co-créatrice du podcast @femigrantespodcast et maman. ❤ Avec Bousso nous avons parlé de maternité et bipolarité. ❤ De la découverte de sa bipolarité ❤ Des circonstances dans lesquelles elle a été enceinte ❤ De la découverte de sa nouvelle relation de mère avec sa fille ❤ De l'équilibre que cette relation lui a apporté 🤎 Quelle belle rencontre pleine de conseils, de rires. Merci à Alice et Agnès pour le montage et pour les illustrations. Le blog de Bousso : Mamma.donnanera
Keywords: 2000 à aujourd'hui; afrique; cours; europe; fem3300; femmes* noires; france; maternité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; santé; santé mentale; sénégal; thématiques